Environment-friendly lawn filling particles and preparation method thereof

By using thermoplastic dynamic vulcanized rubber (TPV) made of biodegradable polymers and plasticizers as artificial turf fill particles, the environmental protection and recycling of existing fill particles is solved, and high-performance and environmentally friendly fill particles are achieved.

CN119842193AActive Publication Date: 2025-04-18ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510129215.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-18
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The existing artificial turf filled particles have environmental pressure. For example, black waste tire particles contain carcinogens, vulcanized EPDM particles are thermoset materials that cannot be recycled and have a rubber odor. Although thermoplastic elastomers are environmentally friendly, they are costly.

Method used

Thermoplastic dynamic vulcanized rubber (TPV) made of biodegradable polymers A and B, plasticizer, peroxide initiator and crosslinking agent are used as fill particles. Internal crosslinking is performed by adding plasticizer and peroxide initiator to form a mesh structure to improve deformation recovery performance, and provide structural support with PLA or PPC.

Benefits of technology

It realizes environmentally friendly, degradable, mechanical properties and hardness controllable filling particles, reduces pollution caused by non-recyclable rubber, and is suitable for filling particles on high-end site lawns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005260977500000041
    Figure BDA0005260977500000041
  • Figure BDA0005260977500000051
    Figure BDA0005260977500000051
  • Figure HDA0005260977510000011
    Figure HDA0005260977510000011
Patent Text Reader

Abstract

The invention discloses environment-friendly lawn filling particles and a preparation method thereof. The environment-friendly lawn filling particles are prepared from the following raw materials: a biodegradable polymer A, a biodegradable polymer B, a plasticizer, a peroxide initiator and an assistant crosslinker, the biodegradable polymer A is PLA or PPC, the biodegradable polymer B is PBAT or PBS, the plasticizer is cardanol ethyl ester or epoxy cardanol ethyl ester, and the assistant cross-linking agent is triallyl isocyanurate. The prepared filling particles have the elasticity and recovery performance of rubber, the mechanical property, hardness and color can be regulated and controlled, and the filling particles can be used as filling particles of lawns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to novel environment-friendly lawn filling particles and a preparation method thereof, and belongs to the research field of polymer materials. Background Art

[0002] Artificial turf originated in the 1960s to solve the maintenance problems of natural turf. It is mainly composed of grass fiber, base fabric and adhesive. Nylon fiber was used at first, and later polypropylene, polyethylene and other materials were used. Its advantages are low maintenance cost, no climate restrictions, and high use intensity. However, it also has limitations such as high surface temperature, poor touch, and environmental protection needs to be improved.

[0003] Filling particles emerged with the development of artificial turf technology. In the early days, sand was used, and later rubber particles were used. Filling particles can enhance the elasticity, cushioning performance and stability of the lawn, reduce sports injuries, and improve drainage and air permeability. There are three main types of artificial turf filling particles on the market: ① black waste tire filling particles; ② vulcanized EPDM filling particles; ③ thermoplastic elastomer particles. Due to its low cost, the largest amount of use at home and abroad is waste tire filling particles. However, black waste tire particles contain carcinogenic polycyclic aromatic hydrocarbons and face greater environmental pressure; vulcanized EPDM particles themselves are thermosetting materials, cannot be recycled, and have a rubber smell; thermoplastic elastomers have become the best choice for filling particles. Summary of the invention

[0004] The purpose of the present invention is to provide an environmentally friendly lawn filling particle and a preparation method thereof.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] In a first aspect, the present invention provides an environmentally friendly lawn filling particle, which is made of raw materials including a biodegradable polymer A, a biodegradable polymer B, a plasticizer, a peroxide initiator and a cross-linking agent. Taking the total weight of the biodegradable thermoplastic phase and the biodegradable rubber phase as 100%, the weight percentages of the biodegradable polymer A and the biodegradable polymer B are 30%-40% and 60%-70% respectively, and the weight amount of the plasticizer is the total weight of the biodegradable polymer A and the biodegradable polymer B. The weight dosage of the peroxide initiator and the cross-linking aid is 10%-20% of the weight of the biodegradable polymer B, and the weight dosage of the peroxide initiator and the cross-linking aid is 0.1%-1% and 0.2%-2% of the weight of the biodegradable polymer B respectively; the biodegradable polymer A is PLA (polylactic acid) or PPC (polypropylene carbonate), the biodegradable polymer B is PBAT (polybutylene adipate / terephthalate) or PBS (polybutylene succinate), the plasticizer is cardanol ethyl ester or epoxy cardanol ethyl ester, and the cross-linking aid is TAIC (triallyl isocyanurate).

[0007] Since the glass transition temperature of PBAT or PBS is only about -30°C, these two materials are in a highly elastic state at room temperature and should be elastomers, but have large irreversible deformation. The present invention adds a plasticizer and uses a peroxide initiator to crosslink the inside into a network to obtain better deformation recovery, and the thermoplastic phase is replaced by PLA or PPC to provide structural support. During dynamic vulcanization, the cross-linking agent will also form a PLA-PBAT grafted product at the interface to improve its mechanical properties; thereby obtaining a thermoplastic dynamic vulcanized rubber (TPV) with adjustable mechanical properties and hardness to serve as filling particles for artificial turf.

[0008] Preferably, the peroxide initiator is BIBP (di-tert-butyl cumyl peroxide) or DCP (dicumyl peroxide).

[0009] Preferably, the weight amount of peroxide initiator and cross-linking agent is 0.1%-0.3% and 0.2%-0.6% of the weight of the biodegradable rubber phase, respectively.

[0010] In a second aspect, the present invention further provides a method for preparing the environmentally friendly lawn filling particles according to the first aspect, comprising the following steps:

[0011] S1: adding a peroxide initiator and a co-crosslinking agent to polymer B, mixing them uniformly at room temperature in a high-speed mixer, extruding and granulating them in a twin-screw extruder, and air-cooling and granulating them to obtain a premix;

[0012] S2: Weigh polymer A and premix according to proportion, mix them in a high-speed mixer, add the mixture into the hopper of a twin-screw extruder, and at the same time, pump the plasticizer into the twin-screw extruder through the vacuum port by a constant flow pump, extrude and granulate through the twin-screw extruder, and air-cool and granulate to obtain environmentally friendly lawn filling particles.

[0013] Since the peroxide initiator reacts with both polymer A and polymer B, the present invention pre-adds the cross-linking agent to polymer B in the first step and mixes them evenly, but does not react. In the second step, the cross-linking agent is dynamically vulcanized simultaneously with polymer A and the plasticizer to ensure that the cross-linking reaction occurs in large quantities in the rubber phase represented by polymer B to provide elasticity.

[0014] Preferably, in step S1, the conditions in the twin-screw extruder are set as follows: the temperature is 110° C.-130° C., and the screw speed is 100-150 rpm.

[0015] Preferably, in step S2, the conditions in the twin-screw extruder are set as follows: the temperature is 150°C-180°C, and the screw speed is 100-150 rpm.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The thermoplastic phase and rubber phase of the present invention are both degradable polyesters, and the plasticizer is also a bio-based plasticizer, which can be self-degraded after being discarded or lost, is environmentally friendly, green and non-toxic, and will not produce precipitation or volatilization of harmful substances.

[0018] 2. Although the present invention is plastic, it has the elasticity and recovery properties of rubber, and its mechanical properties, hardness and color are adjustable. It can be used as filling particles for lawns in some high-end venues, opening up a way to reduce the pollution caused by non-recyclable rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The cyclic tensile diagrams of the filled particles prepared in Comparative Example 1 and Examples 1-4 are shown.

[0020] Figure 2 TEM images of the filling particles prepared in Examples 1, 2 and 4, wherein (a), (b) and (c) correspond to the products of Example 1, Example 2 and Example 4, respectively. DETAILED DESCRIPTION

[0021] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0022] The "parts" mentioned in the present invention, unless otherwise specified, refer to parts by weight.

[0023] In the following examples, the PLA used is REVODE101 (high D-lactic acid content, non-crystallized) purchased from Zhejiang Haizheng Biomaterial Co., Ltd., PBAT is TH-801 from Xinjiang Lanshan Tunhe Co., Ltd., and the plasticizer (epoxidized cardanol ethyl ester) used is purchased from Jiangsu Lianmeng Chemical Co., Ltd. The initiator BIBP and the auxiliary cross-linking agent TAIC are both commercially available industrial-grade reagents.

[0024] Comparative Example 1

[0025] Raw material composition: PLA 30wt%, PBAT 70wt%, epoxidized cardanol ethyl ester 20wt% (percentage of the total mass of PLA and PBAT).

[0026] PLA and PBAT were weighed in proportion and mixed in a high-speed mixer. The resulting mixture entered the extruder through the hopper of a twin-screw extruder (SHJ20, Nanjing Juli Chemical Machinery Co., Ltd.). At the same time, the plasticizer was pumped into the extruder through the vacuum port of the twin-screw extruder by a constant flow pump. The mixture was extruded into strips by the twin-screw extruder and pelletized by air cooling to obtain lawn filling particles.

[0027] The specific temperatures of the twin-screw extruder are (from the feed port to the die): 150°C, 160°C, 170°C, 180°C, 180°C, 170°C, 165°C, 155°C, 155°C; the speed is 150rpm. The flow rate of the constant flow pump is set to 75ml / min.

[0028] Example 1

[0029] Raw material composition: PLA 30wt%, PBAT 70wt%, epoxidized cardanol ethyl ester 20wt% (percentage of the total mass of PLA and PBAT). The amount of BIBP and TAIC used is 0.1%wt and 0.2%wt of the mass of PBAT, respectively.

[0030] S1: Weigh BIBP and TAIC, add them to PBAT, mix them in a high-speed mixer at room temperature for 5 minutes; extrude and granulate them in a twin-screw extruder, and air-cool and granulate them to obtain PBAT premix. The specific temperatures of the twin-screw extruder are (from the feed port to the die): 120°C, 125°C, 125°C, 130°C, 130°C, 125°C, 120°C, 120°C; the speed is 100rpm.

[0031] S2: PLA and PBAT premixes are weighed in proportion and mixed in a high-speed mixer. The resulting mixture enters the extruder through the hopper of the twin-screw extruder. At the same time, the plasticizer is pumped into the extruder through the vacuum port of the twin-screw extruder through a constant flow pump. The twin-screw extruder is used for extrusion granulation and air-cooled granulation to obtain environmentally friendly lawn filling particles. The specific temperatures of the twin-screw extruder are (from the feed port to the die): 150°C, 160°C, 170°C, 180°C, 180°C, 170°C, 165°C, 155°C, 155°C; the speed is 150rpm. The flow rate of the constant flow pump is set to 75ml / min.

[0032] Example 2

[0033] The same as Example 1, except that the amounts of BIBP and TAIC used are 0.2%wt and 0.4%wt of the mass of PBAT, respectively.

[0034] Example 3

[0035] The same as Example 1, except that the amounts of BIBP and TAIC used are 0.3%wt and 0.6%wt of the mass of PBAT, respectively.

[0036] Example 4

[0037] The same as Example 1, except that the amounts of BIBP and TAIC used are 0.4%wt and 0.8%wt of the mass of PBAT, respectively.

[0038] Performance testing and result analysis

[0039] Mechanical properties test

[0040] The tensile test of the samples was carried out on a universal testing machine according to ASTM D882-12. The samples were cut into dumbbell-shaped specimens with a length of 75 mm, a parallel part width of 4 mm, and a thickness of 2 mm. All samples were placed at 20°C and 50% RH for 24 hours. The mechanical properties of the specimens were tested at a tensile rate of 100 mm / min at room temperature. Five samples were measured in each group, and the results were arithmetic averaged. The results are shown in Table 1.

[0041] The sample was subjected to a cyclic tensile test at 50°C with a fixed strain of 50%. The number of cycles was 5. The results are shown in Table 2.

[0042] Table 1 Mechanical properties

[0043]

[0044] The cross-linking agent content has a significant effect on the mechanical properties of TPV. As shown in Table 1, we can see that in the PLA / PBAT blend without the addition of the cross-linking system, the tensile strength is very low, only 7.1MPa. There are two reasons for such low strength. One is because of the influence of the plasticizer. The small molecule plasticizer is embedded in the molecular chain to separate the chain, greatly improving the mobility of the molecular chain, which will lead to a significant decrease in modulus and strength. This is also one of the reasons why the strength of the TPV system is generally not high. Second, because of the incompatibility of the PLA and PBAT systems, the intermolecular bonding force is weak, and the two phases often produce gaps, which significantly affects the strength of the blend. In this work, the cross-linking agent is pre-dispersed uniformly in the PBAT phase. During the dynamic vulcanization process, the cross-linking agent molecules on its surface will react with both PLA and PBAT at the same time, thereby strengthening the interfacial compatibility and significantly improving the mechanical properties. The tensile strength of Examples 1-3 is about 9.3MPa, while the tensile strength of Example 4 is only 7.3MPa, and the elongation at break is also greatly reduced. It can be inferred that this is due to the performance loss caused by excessive cross-linking of PBAT. Therefore, an appropriate degree of cross-linking can maintain the optimal performance of PLA / PBAT-based TPV.

[0045] Table 2 Tensile permanent deformation

[0046] Tensile permanent set at 50% deformation (%) Comparative Example 1 54.0 Example 1 26.3 Example 2 23.3 Example 3 28.7 Example 4 29.3

[0047] To study the deformation recovery ability of PLA / PBAT, the present invention conducted a cyclic stress-strain test at 50% strain. The results are as follows Figure 1 As shown in Table 2, the pure PLA / PBAT blend slips after the molecular chain is stretched, because there is no cross-linking component in it and it cannot provide recovery ability, thus showing a large tensile permanent deformation. The sample with added plasticizer can recover part of it due to the lubrication of the plasticizer, but the effect is not ideal. After adding the cross-linking agent at the same time, the cross-linking component acts as an elastomer, providing elastic recovery and obtaining a lower tensile permanent deformation. Due to the different amounts of cross-linking agent, the stress performance of each sample at 50% strain is also different. After the cross-linking agent content is higher than 0.2, the stress of the sample increases due to the increase in cross-linking density. Compared with the low content of cross-linking agent, the molecular chain is less likely to slip. Under the same strain, more molecular chains are broken, making it more difficult to return to the initial state, which increases the permanent deformation.

[0048] As we all know, the elasticity of TPV is lossy. Unlike rubber or other elastomers, it does not have 100% deformation recovery. After the first stretching, it has a large loss, but the loss will gradually decrease with the number of cycles. The reason is that during the first stretching, the PLA molecular chain as the plastic phase breaks, which is an irreversible deformation. In the subsequent stretching, the broken PLA molecular chains will gradually decrease until a balance is reached.

[0049] Compression set

[0050] The compression permanent deformation of the samples was tested according to GB / T 7759.1-2015. Since the outdoor temperature was not high, we combined the usage scenario with the conditions of temperature 40°C, time 22h, and strain 25%.

[0051] Table 3 Compression set

[0052]

[0053]

[0054] Among them, h0 is the initial height of the sample, h1 is the height of the sample after recovery, and h s is the limiter height.

[0055] Compression set is an important parameter of TPV. It reflects the elasticity and deformation recovery ability of the product. It is a common test method for rubber and thermoplastic elastomers. From the results in Table 3, we can see that the compression set of Comparative Example 1 without adding a crosslinking agent is the highest, reaching 31.7%. As the content of the crosslinking agent increases, a crosslinking network gradually forms in the PLA / PBAT blend, which limits the relative slip between the molecular chains and provides elasticity for the sample. When the product is subjected to external forces, it generates internal stress resistance. After the external force is removed, it relies on the crosslinking network to recover, and the compression set is reduced, up to 14.4%. It is half the size of Comparative Example 1.

[0056] Rebound rate and hardness

[0057] The rebound rate and hardness of the samples were tested according to GB / T 1681-2009 and GB / T 23651-2009 respectively.

[0058] Table 4 Rebound rate and hardness

[0059] Rebound rate hardness Comparative Example 1 43.2% 93.0 Example 1 52.9% 73.0 Example 2 48.5% 72.0 Example 3 49.4% 75.0 Example 4 46.6% 72.5

[0060] Table 5 Rebound rate and hardness of some common rubbers

[0061] Rebound rate hardness Natural rubber About 70% 30-90 Styrene Butadiene Rubber 40%-50% 40-95 Butadiene rubber 70%-95% 30-80 Neoprene 30%-50% 40-90 Silicone Rubber 50%-60% 20-90 Nitrile rubber 20%-50% 40-95

[0062] Resilience and hardness are also important parameters for rubber testing. Table 4 shows the rebound rate and hardness of each comparative example and embodiment. By comparing the rebound rate and hardness of some common rubbers, we can find that the rebound rate is very close to that of rubber, while the hardness is determined according to the needs of different scenarios. The hardness range of various rubbers spans a wide range. The hardness of each embodiment of the present invention is generally around 72, which belongs to a relatively soft range. From the data of these two items, the present invention can basically replace rubber particles in terms of rebound rate and hardness.

Claims

1. An environmentally friendly lawn filling particle, characterized by: The environmentally friendly lawn filling particles are made of raw materials including a biodegradable polymer A, a biodegradable polymer B, a plasticizer, a peroxide initiator and a cross-linking agent. Taking the total weight of the biodegradable polymer A and the biodegradable polymer B as 100%, the weight percentages of the biodegradable polymer A and the biodegradable polymer B are 30%-40% and 60%-70% respectively, the weight amount of the plasticizer is 10%-20% of the total weight of the biodegradable polymer A and the biodegradable polymer B, and the weight amounts of the peroxide initiator and the cross-linking agent are 0.1%-1% and 0.2%-2% of the weight of the biodegradable polymer B respectively; the biodegradable polymer A is PLA or PPC, the biodegradable polymer B is PBAT or PBS, the plasticizer is cardanol ethyl ester or epoxy cardanol ethyl ester, and the cross-linking agent is triallyl isocyanurate.

2. The environmentally friendly lawn filling particles according to claim 1, characterized in that: The peroxide initiator is di-tert-butyl cumene peroxide or dicumyl peroxide.

3. The environmentally friendly lawn filling particles according to claim 1, characterized in that: The weight amounts of the peroxide initiator and the auxiliary cross-linking agent are 0.1%-0.3% and 0.2%-0.6% of the weight of the biodegradable rubber phase respectively.

4. A method for preparing the environmentally friendly lawn filling particles according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: adding a peroxide initiator and a co-crosslinking agent to polymer B, mixing them uniformly at room temperature in a high-speed mixer, extruding and granulating them in a twin-screw extruder, and air-cooling and granulating them to obtain a premix; S2: Weigh polymer A and premix according to proportion, mix them in a high-speed mixer, add the mixture into the hopper of a twin-screw extruder, and at the same time, pump the plasticizer into the twin-screw extruder through the vacuum port by a constant flow pump, extrude and granulate through the twin-screw extruder, and air-cool and granulate to obtain environmentally friendly lawn filling particles.

5. The preparation method according to claim 4, characterized in that: In step S1, the conditions in the twin-screw extruder are set as follows: temperature is 110°C-130°C, and screw speed is 100-150 rpm.

6. The preparation method according to claim 4, characterized in that: In step S2, the conditions in the twin-screw extruder are set as follows: temperature is 150°C-180°C, and screw speed is 100-150 rpm.

Citation Information

Patent Citations

  • Biodegradable thermoplastic elastomer and production method thereof

    CN105802145A

  • Method for plasticizing PLA (Polylactic Acid) by using bio-based plasticizer, PLA plasticizing master batch and application of PLA plasticizing master batch

    CN118745284A

  • PLA / PBAT composite material and preparation method thereof

    CN119286212A

  • Thermoplastic elastomer composition

    US20100016495A1

  • Turf infill material and related turf

    US20240301632A1